Increasing litter species richness reduces variability in a terrestrial decomposer system - Keith, Aidan M; Van der Wal, Rene; Brooker, Rob W; Osler, Graham H.R; Chapman, Stephen J; Burslem, David F.R.P; Elston, David A (Ecology (Durham), 2008)
Debate on the relationship between diversity and stability has been driven by the recognition that species loss may influence ecosystem properties and processes. We conducted a litterbag experiment in the Scottish Highlands, United Kingdom, to examine the effects of altering plant litter diversity on decomposition, microbial biomass, and microfaunal abundance. The design of treatments was fully factorial and included five species from an upland plant community (silver birch, Betula pendula; Scots' pine, Pinus sylvestris; heather, Calluna vulgaris; bilberry, Vaccinium myrtillus; wavy-hair grass, Deschampsia flexuosa); species richness ranged from one to five species. We tested the effects of litter species richness and composition on variable means, whether increasing litter species richness reduced variability in the decomposer system, and whether any richness-variability relationships were maintained over time (196 vs. 564 days). While litter species composition effects controlled variable means, we revealed reductions in variability with increasing litter species richness, even after accounting for differences between litter types. These findings suggest that higher plant species richness per se may result in more stable ecosystem processes (e.g., decomposition) and decomposer communities. Negative richness-variation relationships generally relaxed over time, presumably because properties of litter mixtures became more homogeneous. However, given that plant litter inputs continue to enter the belowground system over time, we conclude that variation in ecosystem properties may be buffered by greater litter species richness.